Social protection: A key instrument for social, economic and political development - Markus Loewe (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2016)
Social protection can be defined as "policies and actions which enhance the capacity of poor and vulnerable people to escape from poverty and enable them to better manage risks and shocks" (OECD/DAC 2009, 10). The term would thus include social insurance, social transfers and minimum labour standards, but for many experts also micro-insurance, commercial insurance and savings plans, traditional solidarity networks and group-based risk prevention instruments.
Keywords: 330